Utilization of Colour-Coded Bins for Management of Solid Waste among Households in Obio Akpor Local Government Area, Rivers State - China, Mercy A.H.; Amadi, Ginika A; Wachukwu, Chikodi H. (Journal of Home Economics Research, 2024)
General objective of the study was to investigate issues relating to utilization of colour-coded bins for management of household solid wasted in Obio Akpor Local Government Area Rivers State. Specifically, the study determined: level of awareness of use of color-coded bins in HSW among households in area of study; level of utilization of colour-coded bins by the households; perceived benefits of use of colour-coded bins among the households; challenges households face in the use of color-coded bins and ways of enhancing the use of colour-coded bins by the households. This study employed survey research design. Population was made up of households in Obio/Akpor LGA. Data was collected with questionnaire. Data were analyzed using mean, frequency, percentages and standard deviation. Results of the study show show awareness levels for five indicators range from 71.92 to 17.85 percent; two colours of bins that are always used are blue (91.86%) and green for organic waste (80.5%); nine benefits of use of coloured bins (X̅ = 3.02 -2.53); 10 challenges (X̅ = 3.23 -2.53) household face in the use of the bins; and nine ways of enhancing utilization (X̅ = 3.27 -2.79). based on the findings three recommendations were made.